Honda Motorcycle Marketing Strategy: Case Study From CV. Anugerah Kencana Motor Palembang, Indonesia - Saleh Usman; T. Trinawati (Manunggal Halim Jaya, 2026)
Marketing is a vital element in maintaining business continuity, especially amidst increasingly fierce competition in the automotive industry. This study aims to analyze the marketing strategy of Honda motorcycles at CV Anugerah Kencana Motor Palembang. The method used is descriptive with a qualitative approach. Data were collected through observation, documentation, and interviews, then analyzed using the marketing mix framework (4P): product, price, place, and promotion. The results show that the company offers various Honda products, such as PCX, Beat, Vario, Scoopy, Genio, and Revo X, with competitive prices and discounts to attract consumers. The business location is considered strategic, although distribution is hampered by limited delivery personnel. Promotion is carried out through personal selling, brochure distribution, and exhibition participation. The company's strategies include market development strategies, product development strategies, defensive strategies, and market penetration strategies. Overall, these strategies help the company increase competitiveness and maintain its business continuity, although further development in distribution and promotional innovation is still needed.